2013
DOI: 10.1007/s11524-013-9821-z
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Alcohol Outlets and the Association with Violent Crime in One Mid-Atlantic City: The Implications for Zoning Policy

Abstract: Violent crime such as homicide causes significant excess morbidity and mortality in US urban areas. A health impact assessment (HIA) identified zoning policy related to alcohol outlets as one way to decrease violent crime. The objectives were to determine the relationship between alcohol outlets including off-premise alcohol outlets and violent crime in one urban area to provide local public health evidence to inform a zoning code rewrite. An ecologic analysis of census tracts in Baltimore City was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 24 publications
3
69
1
6
Order By: Relevance
“…In contrast, liquor stores had elevated mean rates of crime compared with all the other venue types, and the rate of decrease in crime as you moved away from liquor stores was signifi cantly faster than it was for corner stores and treatment centers. This supports the notion that liquor stores are magnets for crime and is consistent with the results of other published studies that have found associations between the presence of liquor stores and elevated rates of violent crime proximal to the store (Gruenewald & Remer, 2006;Jennings et al, 2014;LaVeist & Wallace, 2000;Lipton et al, 2013;Scribner et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, liquor stores had elevated mean rates of crime compared with all the other venue types, and the rate of decrease in crime as you moved away from liquor stores was signifi cantly faster than it was for corner stores and treatment centers. This supports the notion that liquor stores are magnets for crime and is consistent with the results of other published studies that have found associations between the presence of liquor stores and elevated rates of violent crime proximal to the store (Gruenewald & Remer, 2006;Jennings et al, 2014;LaVeist & Wallace, 2000;Lipton et al, 2013;Scribner et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Each one-unit increase in the Neighborhood Disadvantage score is equivalent to an increase of 10 percentage points for each component item of the index (Franklin et al, 2010;Jennings et al, 2014;Ross & Mirowsky, 2001). The total score has a possible range from -5 to +5, where -5 is very low/little disadvantage and +5 is very severe disadvantage.…”
Section: Matching Sites By Neighborhood Disadvantagementioning
confidence: 99%
“…In addition to having negative consequences at the individual level, the increasing number of alcohol outlets in communities may have a negative impact on family members due to alcohol-related violence and crime (Cunradi, Mair, Ponicki, & Remer, 2011;Jennings et al, 2014;Lipton et al, 2013). A study in New Zealand found an association between binge drinking and the density of off-license liquor outlets within easy walking distance of home, with a 4% increase in the odds of binge drinking for every additional outlet (Connor, Kypri, Bell, & Cousins, 2011).…”
mentioning
confidence: 99%
“…Areas of lower socio-economic status, and higher ethnic diversity moderate the alcohol-crime relationship, and tend to experience a greater frequency of crime occurrences [20,37,[77][78][79].…”
Section: Count Of Lighting Structures Per Da Lightsmentioning
confidence: 99%